Social abilities as a factor of individual's successful after-labor socialization - Vlasova, О.; Koskina, D. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article is devoted to the analysis of connection of social abilities' phenomenology among aged people with the peculiarities of their after- labor socialization. The authors attempt to describe positively the after-labor stage through the prism of empirical exploration of the mechanisms of realization individual's potential of social abalities: social creativity and emotional intellect. The article proves that these abilities are key in guaranteeing life's quality and subjective well-being. The elaborated training program allowes significantly improve level of their social creativity, life's quality and subjective well-being in this age.
Keywords: social abilities; late adulthood; socialization; life quality; subjective well-being